Developmental Osteology of Cross‐bred Red Junglefowl (Gallus gallus L. 1758) and the Implications for Ageing Chickens from Archaeological Sites. (14th October 2014) - Thomas, R.; Sadler, P.; Cooper, J.
Abstract: We document the developmental osteology of a captive population of cross‐bred red junglefowl ( Gallus gallus L. 1758) that were slaughtered at known ages from 6 days old until they reached maturity and explore the relationships that exist between bone size, maturity, body weight and sex. In doing so, we contribute to the body of knowledge concerning developmental osteology in domestic fowl, which has previously focussed upon 'improved' breeds. Comparison with archaeological material demonstrates that regression equations developed from the study population to determine age from bone length measurements are unreliable, even when samples with similar mean size for adult birds are compared. However, greater understanding of the maturity of domestic fowl more 'primitive' than most comparative material available for study is used to assist in the assignation of three age classes—chick, immature and adult—and thus facilitate more nuanced analyses of age‐at‐death patterns in faunal assemblages. Copyright © 2014 John Wiley & Sons, Ltd.